Pendinginan Zona Perakaran (Root Zone Cooling) pada Produksi Benih Kentang menggunakan Sistem Aeroponik - Sumarni, Eni; Suhardiyanto, Herry; Seminar, Kudang Boro; Saptomo, Satyanto Krido (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
High temperature is the major constraint to potato cultivation in the lowland for it causes stress and inhibit initiation of potato tuber. This study was designed to investigate the effects of root zone cooling upon seed potato production using aeroponics system in lowland wet tropical climates. Cultivation techniques used in this study was the aeroponics system with three cooling temperatures (10, 15, and 20 oC) and control (greenhouse room temperature). Plantlet of potato ‘Granola’ variety derived from tissue culture propagation were used. The results showed that the highest number of tuber and tuber weight that can be harvested up to 90 days after planting were obtained from cooling the root zone temperature at 10 °C with the average number of tuber 14.85 tubers plant-1and average weight of tubers 409.15 mg tuber-1. Plants grown at root zone cooling at 15 and 20 °C treatments produced lower number of tubers and lower tuber weight than at 10 oC, while plants grown at greenhouse temperature did not produce tubers.Keywords: cultivation techniques, Granola, high temperature, lowland tropical, potato tuber